Analisis Stabilitas Cadangan Devisa di Indonesia - Astuti, Sisca Triyuni; Hidayat, Wahyu (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
Research on foreign exchange reserves is still important, because apart from being a source of development funding, foreign exchange reserves are also as tool to prevent economic crises. The analysis of foreign exchange reserves is developed by looking at the influence of macroeconomic variables such as inflation, exchange rates and foreign debt using the Autoregressive distributed lag model (ARDL) approach. The results show that the independent variable in the model has an effect on foreign exchange reserves in the short term, while in the long term the exchange rate variable has an effect on it. Based on the results of the CUSUM and CUSUMQ tests shows the model is stable. Maintaining economic stability and exchange rate stability is an important agenda for policy makers to create resilient domestic economic conditions in facing crises.